Why "anticipatory action" is required in fragile and conflict settings - Jaime, C.; Attoh, Emmanuel M. N. A. N.; Elgadi, E. (Global Dispatches, 2024)
Today’s episode is produced in partnership with the CGIAR Research Initiative on Fragility, Conflict, and Migration for a series that examines what works to improve the well-being of people in Fragile and Conflict Affected Settings. CGIAR is a global partnership that unites international organizations engaged in research about food security.